Exocytosis of Alphaherpesvirus Virions, Light Particles, and Glycoproteins Uses Constitutive Secretory Mechanisms - Ian B. Hogue; Julian Scherer; Lynn W. Enquist (mBio, 2016)
ABSTRACT Many molecular and cell biological details of the alphaherpesvirus assembly and egress pathway remain unclear. Recently we developed a live-cell fluorescence microscopy assay of pseudorabies virus (PRV) exocytosis, based on total internal reflection fluorescence (TIRF) microscopy and a virus-encoded pH-sensitive fluorescent probe. Here, we use this assay to distinguish three classes of viral exocytosis in a nonpolarized cell type: (i) trafficking of viral glycoproteins to the plasma membrane, (ii) exocytosis of viral light particles, and (iii) exocytosis of virions. We find that viral glycoproteins traffic to the cell surface in association with constitutive secretory Rab GTPases and exhibit free diffusion into the plasma membrane after exocytosis. Similarly, both virions and light particles use these same constitutive secretory mechanisms for egress from infected cells. Furthermore, we show that viral light particles are distinct from cellular exosomes. Together, these observations shed light on viral glycoprotein trafficking steps that precede virus particle assembly and reinforce the idea that virions and light particles share a biogenesis and trafficking pathway. IMPORTANCE The alphaherpesviruses, including the important human pathogens herpes simplex virus 1 (HSV-1), HSV-2, and varicella-zoster virus (VZV), are among the few viruses that have evolved to exploit the mammalian nervous system. These viruses typically cause mild recurrent herpetic or zosteriform lesions but can also cause debilitating herpes encephalitis, more frequently in very young, old, immunocompromised, or nonnatural hosts. Importantly, many of the molecular and cellular mechanisms of viral assembly and egress remain unclear. This study addresses the trafficking of viral glycoproteins to the plasma membrane, exocytosis of light particles, and exocytosis of virions. Trafficking of glycoproteins affects immune evasion and pathogenesis and may precede virus particle assembly. The release of light particles may also contribute to immune evasion and pathogenesis. Finally, exocytosis of virions is important to understand, as this final step in the virus replication cycle produces infectious extracellular particles capable of spreading to the next round of host cells.